A PSYCHOANALYSIS PERSPECTIVE ON THE MAIN CHARACTER'S PSYCHE IN COELHO'S VERONIKA DECIDES TO DIE - Asvika Yuliannisa, - (2008)
This research paper, entitled "A Psychoanalysis Perspective on the Main Character's Psyche in Coelho's Veronika Decides to Die", attempts to find out how the main character's psyche influences her psychological state before she entered Villete Mental Hospital and when she was in the hospital. Therefore, this study investigates the events experienced by the main character before she entered the hospital and when she was in the hospital that are categorized based on the Freud's three components of human psyche-the id, the ego, and the superego. From the discussion, it is found that the novel constructs a main character who suffers because she is oppressed by materialistic society who cares only about material thing such as money rather than immaterial thing such as music. In addition, the power of superego, which had dominated the main character's psyche before she entered Villete Mental Hospital, had made her feel worthless and given no happiness to her life. On the other hand, the dominance of her id when she was in the hospital had given her liberation and made her think that her life is worth living.